Shear strength of RC deep beams with web openings based on two‐parameter kinematic theory. (23rd July 2019) - Liu, Jian; Mihaylov, Boyan
Abstract: Deep concrete beams often feature web openings that disrupt the flow of forces from the loads to the supports and reduce the shear strength of the member. While such openings can significantly impact the safety level of the structure, the research on deep beams has been focused mostly on the shear behavior of solid members. To address this issue, this paper proposes a new model for deep beams with rectangular openings that stems from a two‐parameter kinematic theory (2PKT) for solid beams. The model is established based on an analysis of the shear behavior and failure modes of test specimens using nonlinear finite element and strut‐and‐tie models. In the new model, a deep shear span with an opening is represented by two solid shear spans, one above and one below the opening. By linking the two sub‐models, the proposed kinematics‐based approach describes the complete deformed shape of the shear span with four degrees of freedom (DOFs). These DOFs are predicted by combining the kinematic conditions with equilibrium conditions and constitutive relationships for the mechanisms of shear resistance across the critical shear cracks. The model is validated with 27 tests from the literature showing adequate shear strength predictions.